Refleksi Spiritual dalam Tradisi Asma' Artho untuk Meningkatkan Kesadaran Beragama di Masyarakat Kabupaten Blitar - Bawafi, Habib; Arisiana, Thias; Ikmah, Amit Dana; Khasanah, Khasanah (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study investigates the Asma' Artho tradition in Blitar, Indonesia, as a spiritual practice integrating Islamic teachings with Javanese local wisdom. Employing a qualitative ethnographic approach, the research, through participant observation and interviews, examines the tradition's spiritual elements, its influence on religious awareness, and factors affecting its efficacy and preservation. Data analysis utilizes the Miles, Huberman, and Saldana interactive model. Findings reveal that Asma' Artho, incorporating practices like dhikr and fasting, significantly enhances religious awareness by strengthening ritual observance, spiritual experience, and religious identity. Its effectiveness is influenced by community understanding, leadership quality, and socio-cultural context. Modernization and puritanical critiques pose challenges to the tradition's preservation, while digital adaptation and contemporary reinterpretations offer opportunities for its continuity. This research underscores the dynamic nature of Asma' Artho, highlighting its adaptability within a modern context. It emphasizes the importance of understanding and preserving such traditional practices as integral components of Indonesia's cultural and spiritual heritage.